EFEKTIVITAS TERAPI KOGNITIF PERILAKUAN RELIGIUS UNTUK MENURUNKAN DEPRESI PADA REMAJA - Surayya Hayatussofiyyah; H. Fuad Nashori; Rumiani Rumiani (Psikoislamedia : Jurnal Psikologi, 2017)
The study examined the effectiveness of religious cognitive behavioral therapy to reduce adolescents depression. This study used apretest-posttest control group design. Participants in this study were 12 high school students in Sleman, female, aged 15-16 years and divided into two groups. One group (n = 6) as an experimental group who received treatment in the form of religious cognitive behavioral therapy. One other group (n = 6) as controlled group (waiting list). The scale used in this study was Beck Depression Inventory-II. The results of hypothesis test using non-parametric analyzes such as Mann Whitney U Test to examined the difference in value based on the group, namely the experimental and control. This suggests that there are significant differences in the implementation of post test between the experimental and control group.By using mann whitney, the result concluded that religious cognitive behavioral therapywas significantly effective toto reduce adolescents depression (Z = -2.898, p = 0.004, where p